Gas‐separation behavior of poly(ether sulfone)–poly(ethylene glycol) blend membranes. Issue 44 (23rd September 2018) - Akbarian, Iman; Fakhar, Afsaneh; Ameri, Elham; Sadeghi, Morteza
Abstract : Poly(ether sulfone) (PES), because of its low chain mobility and high gas selectivity, was selected as a gas‐separation membrane. Because poly(ethylene glycol) (PEG) contains polar ether groups favorable for carbon dioxide (CO2 ) capture, we investigated the effects of PEG on the CO2 /CH4 and CO2 /N2 separation properties of PES–PEG blend membranes. PEG with different molecular weights (4000, 6000, and 10, 000) and concentrations of up 30 wt % was added to PES. Scanning electron microscopy and wide‐angle X‐ray diffraction analyses on the blends confirmed the uniformity and dense surfaces of the membranes and no changes in the crystallinity, respectively. Fourier transform infrared spectra indicated good interactions between the PEG and PES segments. Gas permeation tests showed that with increasing PEG molecular weight, its weight fraction permeability of CH4 and CO2 increased, whereas the permeability of O2 and N2 decreased. The best composition of PES–PEG was a 70/30 ratio; with this composition, the selectivities of CO2 /N2 and CO2 /CH4 were enhanced by 64 and 14%, respectively, compared to that of the pure membrane. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46845. Abstract :